Turismo en bicicleta como una alternativa de turismo sostenible en dos zonas rurales de Santo Domingo, en Ecuador - Galarza Pucha, Jairo Patricio (2024)
This study aims to identify the profile of cycle tourists visiting the rural areas of San Gabriel de Baba and Julio Moreno, located in Santo Domingo de los Tsáchilas, Ecuador.Theoretical Framework:Sustainable tourism is defined as an activity that considers economic, social, and environmental factors to ensure the satisfaction of both users and host communities.Method:A descriptive method was employed, applying surveys to four study groups with differentiated questionnaires, revealing heterogeneous variability in the responses.Results and Discussion:The results show that these rural areas significantly contribute to sustainable tourism through bicycle usage. However, respondents highlighted the need to improve road signage and safety for cyclists. This aligns with previous studies in Latin America that emphasize the lack of resources in rural areas for infrastructure and the promotion of sustainable tourism.Research Implications:A lack of precise information is observed, which hinders the development of effective marketing strategies for cycle tourism ventures in these areas. The research is considered preliminary due to the limited information available on tourism in the areas studied and the absence of prior analyses characterizing cycle tourists.Originality/Value:In this regard, the descriptive approach adopted allows for the proposal of tools to promote cycle tourism and improve conditions for local communities, thus enhancing the development of economically viable and environmentally responsible tourism.